2022
DOI: 10.3390/polym14142898
|View full text |Cite
|
Sign up to set email alerts
|

Corn Cob Char as Catalyst Support for Developing Carbon Nanotubes from Waste Polypropylene Plastics: Comparison of Activation Techniques

Abstract: The future and continuity of nanomaterials are heavily dependent on their availability and affordability. This could be achieved when cheap materials are actively employed as starting materials for nanomaterials synthesis. In this study, waste corn cob char was used as support during the preparation of the NiMo catalyst, and the effect of different char-activating techniques on the microstructure, yield and quality of carbon nanotubes (CNTs) obtained from waste polypropylene (PP) plastics using the chemical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Raman spectra for CNTs produced from waste PP and PE showed peaks at 1354 cm -1 for the D-band and 1582 and 1585 cm -1 for the G-band, respectively and 2D-band occurred at 2700 cm -1 . The peaks at 1582 and 1585 cm -1 corresponded to the G-band of graphite carbon, which relates to the vibration of sp 2 -bonded carbon atoms in graphite sheets [36]. The D and G-bands suggested that amorphous and ordered graphitic carbon are present in the synthesized samples.…”
Section: Raman Spectroscopy Of the Produced Carbon Nanotubesmentioning
confidence: 94%
See 1 more Smart Citation
“…Raman spectra for CNTs produced from waste PP and PE showed peaks at 1354 cm -1 for the D-band and 1582 and 1585 cm -1 for the G-band, respectively and 2D-band occurred at 2700 cm -1 . The peaks at 1582 and 1585 cm -1 corresponded to the G-band of graphite carbon, which relates to the vibration of sp 2 -bonded carbon atoms in graphite sheets [36]. The D and G-bands suggested that amorphous and ordered graphitic carbon are present in the synthesized samples.…”
Section: Raman Spectroscopy Of the Produced Carbon Nanotubesmentioning
confidence: 94%
“…The spectra are shown in Figure 5, the spectra are identical with almost all the functional groups occurring at the same wave number. The broad peaks at 3436.54 cm -1 caused by the stretching vibrations of the hydroxyl (-OH) group indicates that water molecule was absorbed by the sidewalls of the CNTs [36], was observed in spectra of both CNTs obtained from PP and PE. The stretching bands of 2847.96 and 2854.77 cm -1 respectively were observed in both spectra which correspond to asymmetric and symmetric C-H of alkanes [37].…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 99%
“…Other features and conditions that could influence catalyst activity and stability are crystallinity, crystalline size, dispersion of metal particles, textural properties and pore geometry, catalyst composition, catalyst preparation method, pre-treatment conditions (calcination and reduction temperatures, etc.) [ 50 , 52 , 53 ].…”
Section: Role Of Catalystsmentioning
confidence: 99%
“…Specifically, biochar has desirable porous structure and contains valuable minerals mostly on its surface, which enhance the catalytic behaviour of the char towards tar conversion and gasification reactions. 175 Biomass naturally contains alkali and alkaline earth metallic species (AAEMs) including K, Na, Ca, and Mg, which generally benefit the gasification process through tar cracking and reforming of tar. These AAEMs also provide additional resistance to carbon deposition and sintering 176,177 by being a good hosting matrix for impregnated a metal catalyst, thus promoting excellent interaction and contact between active metal particles and tar.…”
Section: Challenges Of Tar Production and Strategies For Its Reductio...mentioning
confidence: 99%